You can try them out and see which one works.
a: f(2) = f(1) +6 = 5+6 = 11 . . . . . . not this one
b: f(1) = f(2) -6 = -1-6 = -7 . . . . . . not this one (5 ≠ -7)
c: f(2) = f(1) - 6 = 5 - 6 = -1 . . . . . this gives the right f(2)
d: f(2 = -6(f(1) = -6(5) = -30 . . . . not this one
_____
The appropriate choice is ...
... f(n +1) = f(n) - 6
— — — — —
You can also recognize that the next term is 6 less than the current one, so f(n+1) = f(n) - 6, which corresponds to the 3rd selection.
Answer:
(3,2) I think
Step-by-step explanation:
X= 3
Y=2
3 +2 =5
3-2=1
Answer:
2x^2+4x-16
Step-by-step explanation:
The quadratic can be written as
f(x) = a(x-z1)(x-z2) where z1 and z2 are the roots
f(x) = a (x-2)(x- -4)
a is the leading coefficient
f(x) = 2(x-2)(x+4)
= 2(x^2 -2x+4x-8)
= 2(x^2 +2x-8)
= 2x^2 +4x-16